Adoption patterns of bronchoscopic lung volume reduction procedures in Germany and predicted procedure volumes for other European countries - Pietzsch, Jan B.; Herth, Felix (Respiration, 2019)
Background: Bronchoscopic lung volume reduction (BLVR) using valves and coils has been approved for use since 2003 and 2010, respectively. Objective(s): To study adoption patterns of BLVR in an early-adopting country, and to estimate potential treatment volumes in other European countries. Methods: Therapy- and age-specific volumes for endobronchial valve and coil procedures were obtained from German federal statistics for 2007-2016. Therapy-specific and total BLVR procedure volumes and growth were computed, and patterns in treatment age and device utilization analyzed. Patient volumes for other European countries were predicted using mean German patient volumes of the last 3 data years and age-specific population and emphysema incidences. Results: Over the study period, annual BLVR procedure volumes grew from 91 to 2,053 (+2,256%), reaching a peak of 2,556 procedures in 2013. Coil procedures constituted 36% of the total volume in 2016. Treatment age was stable over time, with highest procedure counts in age group 60-64 years for valves and 65-69 years for coils. A limited increase in device use per procedure was observed. For Germany, 1,655 newly treated BLVR patients were estimated per year, approximating about 5% of the annual newly diagnosed severe emphysema cases. Predicted volume estimates for other European countries ranged from 1 for Liechtenstein to 1,226 for France. Conclusions: Analysis of German procedure data show pronounced BLVR therapy uptake in the early years of adoption, with the more recently introduced coil therapy used in about one-third of patients. Estimated patient volumes to date constitute only a small fraction of the severe emphysema population.